ARCHITECTURE FLOATING ON BUILDINGS FOR ADAPTATION TO GLOBAL WARMING - RAMADHANINGSIH, WULAN DWI; Marina, Nurul Fitria (Jurusan Arsitektur UPR, 2024)
The Earth currently needs to be prepared for sea level rise, both the Earth is threatened by the effects of global warming which has been an issue the world has been facing for a long time. One of them is the melting of ice at the Earth's poles, causing sea levels to continue to rise every year or known as Sea Level Rising. The current architecture needs to pay attention to these conditions In an architectural effort to provide solutions in dealing with natural phenomena, several methods are carried out. The initial step is to carry out comparative studies related to the phenomena and solutions that are being carried out. Then it is necessary to design the concept of the floating building Besides design, further efforts need to be made such as the technology used to make it easier for the building to float automatically when sea level rises or floods occur, materials that are able to adapt to sea water where sea water is alkaline.